Characteristics of Gas Compositions in Giant Gas Fields of China. Issue 4 (August 2014) - Gong, Deyu; Huang, Shipeng; Wu, Wei; Yu, Cong; Fang, Chenchen; Liu, Dan
By the end of 2011, altogether 48 giant gas fields with each proven reserves over 300×10 8 m 3 had been discovered in China. After studying on the main molecular compositions (methane, heavy hydrocarbon gases, nitrogen, carbon dioxide and hydrogen sulfide) of 1170 gas samples in these gas fields, it is found that: a). Alkane gases dominate the molecular compositions of the natural gases; the extremely low content of them have a tight relationship with the extremely high content of non-hydrocarbon gases; methane accounts for 60.1% of the alkane gases. b). Carbon dioxide has the average content of 4.09%; carbon dioxide with an extremely high content (>50%) is mainly distributed in Dongfang1–1, Changling and Songnan gas fields; highly concentrated CO2 in the former one was crustal-derived while that in the latter two was mantle-derived. c). Nitrogen has an average content of 3.56% which is quite low; highly concentrated nitrogen (<20%) is mainly distributed in Hetianhe, Tazhong, Ledong22–1 and Dongfang1–1 gas fields which are organic-originated. d). Hydrogen sulfide has been detected in 12 giant gas fields, with the content of 4.91% in average; the Triassic is the most centralized zone for hydrogen sulfide while the Sichuan Basin has the largest number of sour gas fields and sour gas bearing zones; 7 sour gas fields of high H2 S content (2% ∼ 70%) are found which are resulted from the thermochemical sulfate reduction (TSR).